Improvement of semen quality after treatment with folic acid and zinc in subfertile men in a tertiary hospital - Begum, Nurjahan; Anwary, Shaheen Ara; Alfazzaman, M.; Mostofa, Munshi Akid; Mahzabin, Zeenat; Rahman, M. M. Mafizur; Akter, Mahbuba; Iqbal, Kazi Sohel; Akhter, Rehena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The 50% of all male infertility is idiopathic, and there is currently no recognized treatment. The effectiveness of a nonprescription nutraceutical comprising eight nutrients on sperm quality in males with idiopathic infertility was studied. The aim of the study was to evaluate improvement of semen quality after treatment with folic acid and zinc in subfertile men. Methods: This prospective observational study was carried out in the infertility unit, department of obstetrics and gynaecology, Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka, Bangladesh from January 2018 to June 2020. Approval from local ethics committee was obtained for this study. Results: One hundred and twenty-five male subfertile patients were included in this study. Most men, 99 (79.2%) belong to more than 30 years, followed by 26 (20.8%) less than 30 years, range was 25 to 50 years. Mean ± SD age was 35.3±5.1 years. Rapid linear (RL) before treatment were 16.06±14.46 (mean ± SD) and after treatment were 22.82±13.40 (mean ± SD). Slow linear (SL) before treatment were 17.56±12.06 (mean ± SD) and after treatment were 19.75±9.25 (mean ± SD). Non progressive (NP) before treatment were 10.82±8.95 (mean ± SD) and after treatment were 10.12±7.34 (mean ± SD). Morphology of the sperm before treatment were 19.43±15.48 (mean ± SD) and after treatment were 30.18±19.12 (mean ± SD). Conclusions: Our research findings fully correspond to the above research results, so it can be said that treatment of subfertile men with micronutrients like folic acid and zinc sulfate causes increase of semen quality and thus plays a key role in treatment of male subfertility.